Systemic didactic strategy with e-activities in the development of formative evaluation (Technological Innovations Journal, 2022)
The purpose of this article is to design a systemic didactic strategy with e-activities for the development of formative evaluation, for which we proceeded to the extraction of documentary and bibliographic information managed by the technological tool Perish, inductive - deductive theoretical methods, analysis - synthesis; in addition, a diagnosis based on a survey of students with the reliability of the instrument through Cronbach's Alpha, denoting an unfavorable application of formative evaluation that interacts with students in their learning. For which it is proposed as a systemic process based on the Theory of Systems: Input, Process, Output, Feedback; same that describes the didactic strategy with the following phases: Diagnosis, Resource, Design, Planning, Execution, Evaluation, Results, Analysis and Redesign in this way a cycle of continuous improvement is inserted, it gives importance to the development of formative evaluation through e-activities with student’s participation.
Keywords: didactic strategy; e-activities; formative evaluation; systemic